Development of CRISPR/Cas9 mediated virus resistance in agriculturally important crops. Issue 3 (4th May 2017) - Khatodia, Surender; Bhatotia, Kirti; Tuteja, Narendra
ABSTRACT: Clustered regulatory interspaced short palindromic repeats (CRISPR)/CRISPR associated nuclease 9 (Cas9) system of targeted genome editing has already revolutionized the plant science research. This is a RNA guided programmable endonuclease based system composed of 2 components, the Cas9 nuclease and an engineered guide RNA targeting any DNA sequence of the form N20-NGG for novel genome editing applications. The CRISPR/Cas9 technology of targeted genome editing has been recently applied for imparting virus resistance in plants. The robustness, wide adaptability, and easy engineering of this system has proved its potential as an antiviral tool for plants. Novel DNA free genome editing by using the preassembled Cas9/gRNA ribonucleoprotein complex for development of virus resistance in any plant species have been prospected for the future. Also, in this review we have discussed the reports of CRISPR/Cas9 mediated virus resistance strategy against geminiviruses by targeting the viral genome and transgene free strategy against RNA viruses by targeting the host plant factors. In conclusion, CRISPR/Cas9 technology will provide a more durable and broad spectrum viral resistance in agriculturally important crops which will eventually lead to public acceptance and commercialization in the near future.